Impact of anti-inflammatory drug consumption in peritonsillar abscesses: a retrospective cohort study. Issue 1 (December 2016) - Feasson, Thomas; Debeaupte, Mathilde; Bidet, Clément; Ader, Florence; Disant, François; Ferry, Tristan; Chidiac, Christian; Valour, Florent
Abstract Background The experience of clinicians in charge of the in-hospital management of peritonsillar abscesses supports the association between severe forms and anti-inflammatory drug (AID) consumption. However, this observation is based on a limited number of clinical studies. Our objective was to assess the prevalence and impact of AID consumption in patients with peritonsillar abscesses. Methods All patients referred to the ear, nose and throat surgery department for a peritonsillar abscess were included in a retrospective cohort study (2012–2014). Results Among the 216 included patients (male, 55 %; median age, 32 years [IQR, 26–40]), 127 had received AID (59 %), including corticosteroids (n = 67, 31 %) and/or non-steroidal AIDs (NSAIDs, n = 76, 35 %). 199 patients (92 %) benefit from a puncture and 5 (2 %) from a surgery under general anesthesia, associated with ceftriaxone/metronidazole (51 %) or amoxicillin/clavulanic acid (46 %). An iterative surgical procedure was required in 93 cases (43 %), including 19 % under general anesthesia. Bacteriological analysis (79 %) mainly disclosed streptococci (66 %) of A (18 %) and/or milleri (33 %) groups. The prevalence of anaerobes was higher in patients using AIDs (46 % versus 29 %, p = 0.034), regardless of prior antibiotic therapy. 65 patients benefited from a CT-scan; AID consumption was associated with larger abscesses (6.8 [IQR, 3.7–12.7] versus 2.9 [IQR, 0.9–7.8] cm3 ;p = 0.005). AID consumption was not a risk factor of iterative surgical procedure. Conclusions In comparison to the prescribing habits in uncomplicated upper respiratory tract infection, the high prevalence of AID consumption in patients with peritonsillar suppuration suggests a role of AIDs in promoting these complications.